Pendampingan Penulisan Artikel Best Practice bagi Musyarawah Guru Mata Pelajaran Bahasa Inggris - Yansyah Yansyah; Hafizhatu Nadia; Tenny Murtiningsih (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Every teacher has their own unique experiences and stories in helping their students to achieve their best in studying. Those experiences would be very beneficial if they can share those best practices to other teachers and educational practitioners. Unfortunately, it is hindered for teachers do not write those good practices in a best practice article because of particular reasons, including their lack of skill for writing such article. This paper aims to report a community service in form of a training on writing a manuscript attended by the English local teacher forum coming from various cities in South Kalimantan, Indonesia. Eighteen participants were participated in this one-month training. The program was divided into two types of activities, namely training and mentoring. The training was conducted in one day aimed to introduce and to analyse samples of good articles, which were accepted in reputable international journals, so the participants could learn the characteristics and the structure of the good articles. Meanwhile, the mentoring was carried out for one month in form of weekly virtual mentoring to guide the participants write their articles step-by-step. Questionnaire and interview were utilized to record the data regarding the evaluation of the program. The findings show that the teachers got benefit from this mentoring. They understand what a best practice article is and how to write it. In the end of the program, two out of five teams successfully completed the mentoring and published their article in a national journal. Some barriers during the training and mentoring are also discussed in this article.